Spleen Swabs for Sensitive and High-Throughput Detection of African Swine Fever Virus by Real-Time PCR - Christopher Cafariello; Kalhari Goonewardene; Chungwon J. Chung; Aruna Ambagala (Viruses, 2024)
African swine fever (ASF) continues to spread in Africa, Europe, Asia and the island of Hispaniola, increasing the need to develop more streamlined and highly efficient surveillance and diagnostic capabilities. One way to achieve this is by further optimization of already established standard operating procedures to remove bottlenecks for high-throughput screening. Real-time polymerase chain reaction (real-time PCR) is the most sensitive and specific assay available for the early detection of the ASF virus (ASFV) genome, but it requires high-quality nucleic acid extracted from the samples. Whole blood from live pigs and spleen tissue from dead pigs are the preferred samples for real-time PCR. Whole blood can be used as is in nucleic acid extractions, but spleen tissues require an additional homogenization step. In this study, we compared the homogenates and swabs prepared from 52 spleen samples collected from pigs experimentally inoculated with highly and moderately virulent ASF virus strains. The results show that not only are the spleen swabs more sensitive when executed with a low-cell-count nucleic acid extraction procedure followed by real-time PCR assays but they also increase the ability to isolate ASFV from positive spleen samples. Swabbing is a convenient, simpler and less time-consuming alternative to tissue homogenization. Hence, we recommend spleen swabs over tissue homogenates for high-throughput detection of ASFV by real-time PCR.